NÍVEL DE ENTENDIMENTO DOS CIDADÃOS BRASILEIROS SOBRE AS MEDIDAS DE BIOSSEGURANÇA NO COMBATE À COVID-19 - Ferreira, Grasiele Cristine; Silva, Dayane Jhenifer Ribeiro; Alves, Milena O.; Sousa, Sabrina R. de; Pessoa, Isabela Maria Braga Sclauser (Sinapse Múltipla, 2020)